Entrepreneurial Leadership of Kyai and Its Role in Shaping Santri Entrepreneurship - Sukarji, Sukarji; Zuhri, Zuhri (JURNAL AL-TANZIM, 2026)
The purpose of this study is to analyze Kyai's innovative leadership in fostering student entrepreneurship in Islamic boarding schools. This study uses a qualitative case study design. Data collection was conducted through interviews, observation, and documentation. Data analysis techniques include data condensation, data presentation, and drawing and verifying conclusions. The results show that Kyai’s innovative leadership successfully fostered student entrepreneurship through various entrepreneurial projects and innovative learning models. This leadership also contributed to significant institutional development, including the establishment of collaborations with national and international partners. This study shows that innovative leadership can be an effective model in improving entrepreneurship and the quality of education in educational institutions. This study implies that educational institutions can adopt innovative leadership models to strengthen student independence. In addition, this study emphasizes the importance of external collaboration in improving the quality and reputation of educational institutions.